Beta-Amyloid Downregulates MDR1-P-Glycoprotein (Abcb1) Expression at the Blood-Brain Barrier in Mice. (17th May 2011) - Brenn, Anja; Grube, Markus; Peters, Michele; Fischer, Andrea; Jedlitschky, Gabriele; Kroemer, Heyo K.; Warzok, Rolf W.; Vogelgesang, Silke
Abstract : Neurovascular dysfunction is an important component of Alzheimer's disease, leading to reduced clearance across the blood-brain barrier and accumulation of neurotoxic β -amyloid (A β ) peptides in the brain. It has been shown that the ABC transport protein P-glycoprotein (P-gp, ABCB1) is involved in the export of A β from the brain into the blood. To determine whether A β influences the expression of key A β transporters, we studied the effects of 1-day subcutaneous A β 1-40 and A β 1-42 administration via Alzet mini-osmotic pumps on P-gp, BCRP, LRP1, and RAGE expression in the brain of 90-day-old male FVB mice. Our results demonstrate significantly reduced P-gp, LRP1, and RAGE mRNA expression in mice treated with A β 1-42 compared to controls, while BCRP expression was not affected. The expression of the four proteins was unchanged in mice treated with A β 1-40 or reverse-sequence peptides. These findings indicate that, in addition to the age-related decrease of P-gp expression, A β 1-42 itself downregulates the expression of P-gp and other A β -transporters, which could exacerbate the intracerebral accumulation of A β and thereby accelerate neurodegeneration in Alzheimer's disease and cerebral β -amyloid angiopathy.